2005
DOI: 10.1080/14017430410004623
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood monocyte activation during coronary artery bypass grafting with or without cardiopulmonary bypass

Abstract: It is concluded that the circulating monocyte population is activated during and as a consequence of CABG. There were few apparent additional effects of CPB found in this study. In this setting the inflammation caused by the surgery procedure per se probably surpasses the impact of the CPB on circulating blood monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…On the contrary, in a recently published RCT to investigate the impact of CABG on peripheral monocytes and to evaluate the additional effect of CPB, Wehlin et al 20 demonstrated that during surgery there was a selective decrease in the proportion of CD16+/CD14+ monocytes compared to total monocytes. These had returned to preoperative values 24 hours after surgery, while the total number of monocytes had increased more than 100%.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…On the contrary, in a recently published RCT to investigate the impact of CABG on peripheral monocytes and to evaluate the additional effect of CPB, Wehlin et al 20 demonstrated that during surgery there was a selective decrease in the proportion of CD16+/CD14+ monocytes compared to total monocytes. These had returned to preoperative values 24 hours after surgery, while the total number of monocytes had increased more than 100%.…”
Section: Resultsmentioning
confidence: 97%
“…Serum levels of MCP‐1 decreased during surgery as did soluble CD14, both with increased levels again the day after surgery. Based on these findings, Wehlin et al 20 concluded that the inflammation caused by the surgery procedure per se probably surpasses the impact of the CPB on circulating blood monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…This drop could be explained by the selective entrapment of activated myeloid cells on the surfaces of CPB circuites. Indeed, such selective decrease, particularly population of CD16/CD14 + monocytes during "on-pump" surgery, was reported by Wehlin et al (19).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have demonstrated activation of monocyte functions during CPB 12,25 . The activation of monocytes is naturally associated with altered membrane molecule expression and enhanced cytokines production.…”
Section: Discussionmentioning
confidence: 99%